Cryo-EM structures of ρ1 GABAA receptors with antagonist and agonist drugs - Chen Fan; John Cowgill; Rebecca J. Howard; Erik Lindahl (Nature Communications)
Abstract The family of ρ-type GABAA receptors includes potential therapeutic targets in several neurological conditions, and features distinctive pharmacology compared to other subtypes. Here we report four cryo-EM structures with previously unresolved ligands, electrophysiology recordings, and molecular dynamics simulations to characterize binding and conformational impact of the drugs THIP (a non-opioid analgesic), CGP36742 (a phosphinic acid) and GABOB (an anticonvulsant) on a human ρ1 GABAA receptor. A distinctive binding pose of THIP in ρ1 versus α4β3δ GABAA receptors offers a rationale for its inverse effects on these subtypes. CGP36742 binding is similar to the canonical ρ-type inhibitor TPMPA, supporting a shared mechanism of action among phosphinic acids. Binding of GABOB is similar to GABA, but produces a mixture of partially-locked and desensitized states, likely underlying weaker agonist activity. Together, these results elucidate interactions of a ρ-type GABAA receptor with therapeutic drugs, offering mechanistic insights and a basis for further pharmaceutical development.